GOOGLE DOCS IMKONIYATLARIDAN TA’LIM JARAYONIDA FOYDALANISH VA GOOGLE FORMSDA ONLAYN TESTLAR YARATISH - Allamuratova, V.Z. (SCIENCE and SOCIETY, 2022)
"Using the capabilities of Google Docs in the educational process" is recommended for practical application today in teaching computer science and information technology at a distance education format.